Pelatihan Internet Sehat Sebagai Antisipasi Cyber Bullying Anak Remaja di Panti Asuhan “Kemala Puji” Bandar Lampung - KURNIA FADILA; Hary Sabita; Anandha Sartika Putri; Joko Triloka (Jurnal Pengabdian Masyarakat Madani, 2021)
The background of foster children in Kemala Puji orphanage are mostly from poor families, orphans, neglected, and homeless child. The institution have been serve, nurture, and empower by providing them a sufficient living. Hence, it still needs a better improvement. This is because these children deserve to be made for the next generation. This activity aims to rise of social care between humanity in adolescents, especially for children in the orphanage. This have been done by imparting knowledge to them about healthy internet. Moreover, its increases understanding how to use the internet more healthily, properly and to anticipate of cyber bullying against them. The outcome of training activities are the youth children have been understood how to use a healthy internet, and they have been sufficient skills how to use internet which was given during the training.